Ultra high spatial resolution SIMS with cluster ions — approaching the physical limits. (6th July 2012) - Kollmer, Felix; Paul, Wolfgang; Krehl, Martin; Niehuis, Ewald
<x xml:space="preserve">Abstract</x> We present state‐of‐the‐art time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS) imaging with Bi primary ion clusters. The latest technological step pushes the lateral resolution into a region which has previously not been attained even by bombardment with mono‐atomic primary beams. We show high lateral resolution TOF‐SIMS images of line structures on certified reference samples and of real world samples. Moreover, we analyzed buried objects by prior removal of the covering material with the Bi cluster beam. Subsequent SIMS analysis of the vertical crater wall achieves a lateral resolution in the sub 50‐nm range at a depth of about 20 µm. Copyright © 2012 John Wiley & Sons, Ltd.